Ekonomi dan Kewarganegaraan Analisis Dampak Investasi Asing terhadap Kebijakan Kewarganegaraan di Indonesia - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Ilham Thoriq Hidayatullah; Kamelia Zahra Ardiani; An nisaa Nur Sifa Az Zahra (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
This study aims to analyze the impact of foreign direct investment (FDI) on citizenship policies in Indonesia and explore how changes in these policies can affect citizens' rights and national sovereignty. The research uses a qualitative approach with a literature review method. A literature review is a type of research conducted by collecting and analyzing existing data or scholarly articles to address problems and understand fundamental issues. The reason for using library research is that the researcher needs data from various sources such as books and previous research journals. Using this method, the researcher identifies relevant topics aligned with the research goals and then analyzes journals and books to answer questions about how FDI significantly impacts Indonesia's economy, driving growth, job creation, and global competitiveness. However, citizenship policies related to FDI require careful attention to balance investment needs with national sovereignty. Reforming policies to simplify residency and citizenship status for foreign investors could make Indonesia a more attractive investment destination, but it might also raise concerns about the impact on the rights of native citizens and national integrity. To manage these effects, Indonesia needs to develop integrated citizenship policies, conduct regular evaluations, enhance transparency, and learn from international practices. With a careful approach, Indonesia can maximize the benefits of FDI while maintaining national interests.